Undetectable TSH could be a TSH variant; case of a young asymptomatic Nepalese male - Pradhan, Santosh; Pant, Vivek; Gautam, Keyoor; Pyakurel, Devish; Shrestha, Abha (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Thyroid function tests are frequently ordered test. Infrequently, the automated thyroid hormone assay system is subjected to interference which may yield false results, thus leading to inappropriate diagnosis and management. We report an unusual case of clinically misdiagnosed subclinical hyperthyroidism with undetectable TSH due to negative interference in particular TSH assay platforms in a young Nepalese male.